Technological development roles and needs in pre-hospital emergency care from the advanced level paramedics’ perspective - Rinkinen, Tuomo (Elsevier, 2025)
Introduction: The work environment of paramedics is rapidly becoming more technology-oriented, and new innovations are constantly being introduced. The aim of this study was to determine the roles Finnish advanced level paramedics identify for themselves within technological development processes in their experience and what kinds of technological development in pre-hospital emergency care are needed.
Methods: This qualitative study utilised essay material written by experienced advanced level paramedics (n = 20), which was analysed using inductive content analysis.
Results: The paramedics identified direct and indirect roles and clear obstacles. The roles were related to expertise, their own professional skills, supporting development and implementation. The obstacles to participation in technological developed were perceived as the employer's unwillingness to involve grassroots level paramedics, lack of training or expertise, and overall unrecognised role. Technological development was seen to be needed regarding information and communication technology, treatment tools, and equipment. Further, nationally homogenous technological development that supports the quality and safety of nursing work and the integration of digitalization into education were also seen as needed.
Conclusions: Paramedics can be innovative and active technology developers with extensive expertise in the technology of their field. Employers and technology developers should be encouraged to enable user-oriented product development and to involve paramedics in development work.